Esensi Hidup dan Mati dalam Pandangan Islam dan Buddha - Azizy, Orry Anas (Lembaga Yasin AlSys, 2023)
In Indonesia, there are five recognized religions, including Islam and Buddhism. Both of these religions believe in the end of life or death. However, each religion has different teachings in providing guidance for life to its people. Likewise in matters of charity and worship. This research raises the issue of how the essence of life and death is the view of Islam and Buddhism. The discussion of this thesis uses theological approach method. Researchers used a descriptive qualitative research method with a comparative theory approach (comparison). The result of this study is that death in Buddhism and Islam has differences. In Buddhism, it means the end of the life of the human organs with the destruction of the body or body, while in Islam, death is a separation between the spirit and the body. Regarding the nature of death, Buddhism and Islam have the same meaning. In essence death is the process of moving humans from one realm to another, but both are different about nature. In the view of Buddhism and Islam, life after death is the revival of humans to continue life in order to achieve the desired goals. In Buddhism, that goal is the attainment of happiness in the form of eternal nibhanna. Meanwhile, what Islam wants to achieve is happiness in the form of eternal heavenly pleasures and this can be achieved with the good pleasure of Allah.